#TITLE_ALTERNATIVE# - HADRIJANTIE SUDJONO (NIM: 32407001); Tim Pembimbing: Prof. Safwan Hadi, Ph.D; Dr.Eng. Nining Sa, EVIE
Shallow waters tidal constituents are components that are formed through interaction of the major tidal components caused by bottom friction and change of velocities in space (convective terms). Strait of Malacca is one of the shallow waters in which the dynamics of its shallow water tidal components have not yet been studied. In this dissertation, the dynamics of shallow waters tidal components i.e. M4 and M6 in the Malacca Straits have been studied using non linear two-dimensional hydrodynamics model and Conjugate Gradient Least Squares (CGLS) iterative assimilation method. The hypothesis of this dissertation is the shallow waters tidal wave which propagates into the Malacca Strait as Kelvin wave is thought to change into Poincare wave. So the assumption used is the shallow waters tidal waves (M4 and M6) are generated by giving M2 wave at the open boundary. In addition, mean sea level used as a reference level is assumed to be constant in space and time. By applying the assimilation method, errors of simulated amplitude and phase of M4 resulted from forward model can be reduced by 94% and 22% respectively . The simulated results were compared with field data at two stations (Bagan Siapi-api and Karimun Besar). The results of the assimilation model showed that the amplitude of the M4 ranged from 0.02 to 0.29 m and at some stations its amplitude is greater than the amplitude of the major tidal components O1. This proves the important role of the shallow waters component M4 in the study area. While, quantitatively, the simulation results of the tidal component M6 has not shown satisfactory results. In the Malacca Strait the shallow waters tidal waves M4 and M6 propagate from north to south. In its propagation the M4 undergoes the change in amplitude starting from 0.02 m in the north around Penang and increased the amplitude due to the effect of shoaling and narrowing the strait to 0,13 m at Belawan and then 0.15 m at Tanjung Balai and reached 0.24 m at Tanjung Medang - Rupat Island. While, around north of Tanjung Parit - Batu Pahat the velocity increased from 0,22 m/s to 0,43 m/s accompanied with decreasing of the amplitude to about 0.08 m. The propagation of M4 and M6 as modified Kelvin wave to Poincare wave occurred in shallow depth at the central part of the Malacca Strait around southeastern of Port Dickson and around the Batu Pahat. Change in these waves types is indicated by the change of the current ellipse in which flattened ellipse (which means waves propagate in one direction/parallel to the coast) turns into ellipse with enlarged short axis which indicates the wave is no longer propagates in one direction as Kelvin wave. The modified Kelvin wave can also be seen from the amplitude of the wave which is greater in the western coast of Malaysia than of the eastern coast of Sumatera. The same condition is also seen in the propagation of M2 wave. The general conclusion of this dissertation is first, the assimilation method tends to improve the results of the non linear horizontal two-dimensional numerical model in the Strait of Malacca. Second, this research has proven the proposed hypothesis. Contribution of this research to the development of the science of oceanography is knowledge of the dynamics of shallow waters tidal components in the Malacca Strait. While in the field of applied science is to improve the accuracy of tidal prediction in this strait (to take into account the shallow water tidal constituent M4).